The McSpeight file : Satire on the Speight Crisis 2 - Craddock, Patrick (Pacific Journalism Review : Te Koakoa, 2002)
There will be enough burgers for all of the poor Tailevu and surrounding districts. All customers are required to pay cash for in advance for their burgers. No cheques or credit cards please.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnY4aTEuNzI5